A comparative assessment of flexibility of backline and strength of lower limb in bharatnatyam dancers and non-dancers - Otari, Shreya M.; Puntambekar, Anjali (International Journal Of Community Medicine And Public Health, 2021)
Background: Bharatnatyam is an Indian classical dance form which have been practiced for a long period of time and is equivalent to any sporting activity. The postures attained during this dance form require good amount of muscle strength and flexibility among the dancers. There is lack of research on flexibility of backline and lower limb strength in bharatnatyam dancers. The overall function of the superficial backline is to support the body in full upright extension and impacts musculoskeletal dynamics. The lumbar lordosis angle and the pelvic inclination angle in bharatnatyam dancers is more than the non-dancers which can affect the backline flexibility. This study analysed if there is any difference, in the lower limb strength and flexibility of backline as compared to participants of same age group. Methods: 10 bharatnatyam dancers and 10 non-dancers between 15 to 30 years participated in this study. Triple hop distance test for both sides and toe touch test was used to check the strength of lower limb and flexibility of backline respectively. Results: There was significant difference in the triple hop distance of right lower limb between bharatnataym dancers and non-dancers. There was no significant difference in the triple hop distance of left lower limb between the two groups. There was not quite significant difference in the toe touch test of between the two groups. Conclusions: There was significant difference in the strength and power of right lower limb of dancers as compared to right lower limb of non-dancers. There was no statistical difference in the left lower limb of both the groups. There was no statistical difference between the flexibility of backline of bharatnatyam dancers and non-dancers.